The right to a 'world class city'?: street trading, public space and urban governance in the Cape Town city centre - Horber, Jens (School of Architecture, Planning and Geomatics, 2018)
There is a long history of street trading restriction in South Africa, and the relocation of traders from key public spaces in Cape Town, in connection with renovation and construction for the 2010 FIFA World Cup, highlighted the contested nature of street trading in the Cape Town city centre. The Grand Parade, South Africa's oldest public space, sits adjacent to the city's major public transport hub, and plays a vital role in the daily lives of many city residents. Therefore, public space contestations, and the informal sector's importance in job creation and poverty reduction, necessitate an investigation into the impacts of the City of Cape Town's street trading management approach on the livelihood strategies of traders on the Parade. I review relevant literature on street trading management, and develop criteria for assessing the City of Cape Town's street trading management approach. These criteria are linked to Lefebvre's (1968) and Fainstein's (2010) concepts of 'the right to the city' and 'the just city' respectively. The main research question thus asks: What is the impact of the City of Cape Town's street trading management approach on the livelihood strategies of traders on the Grand Parade? The research uses the case study and discourse analysis methods to address this question. Data is collected through nonparticipant observation and individual semi-structured interview techniques. The focus is on capturing the views and experiences of traders on the Grand Parade. The research findings indicate that the City of Cape Town tends to adopt a more restrictive approach to managing traders on the Grand Parade, and that this has, effectively, a negative impact on trader livelihoods. This approach serves to produce informal arrangements, aggression and resistance on the part of traders. A disjuncture is found between the stated developmental approach of the City's Informal Trading Policy (informed by national developmental policies) and its practices. The combination of organisational restructuring processes, confused mandates as well as the low political and funding priority given to street trading management has meant that the complex of socio-economic factors and persistent management issues on the Parade, that require interdepartmental cooperation to address, continue to negatively impact trader livelihoods. I recommend that the City of Cape Town, in line with the aims contained in its Informal Trading Policy, and inspired by the 'eThekwini model', implement a more progressive street trading management approach that is based on participatory and area-based approaches. A dedicated focus on capacitating trader organisations through training initiatives is recommended, as well as changes to trading permit application processes and conditions. Lastly, specific recommendations are also made to better enable livelihood strategies of street traders on the Grand Parade.